Literary Routes: Contributions to Natural/Cultural Heritage Tourism. How landscape transforms literature and tourism - Rosalinda Ruiz Scarfuto (University of Bologna, 2013)
Literary routes inspired by landscapes is a topic where cultural and natural routes merge to form an added value of heritage that is greater than either one standing alone. Landscape is traditionally defined as a consequence of transformations by humans, and its scope rarely takes into account how nature has inspired literature to advance the “intellectual development of humankind,” hence transforming heritage. Literary routes paralleling transhumance routes embraced by the Sami, First Nations, or Spanish shepherds (full of landscapes, seascapes, and riverscapes), can actively transmit traditional technologies, biodiversity, and cosmic philosophy for the betterment of humankind; for example, the depth of literary heritage inspired by landscapes enhances our collective memory through a network of archives (libraries, collections). The continuous dissemination of this literature traversing borders, language barriers, and time periods has stimulated literary routes to emerge as a function of moving the experience from an intangible heritage based on imaginary landscapes to a tangible sensory experience in situ following a plot, author’s life, or a myth. Literary routes respond to the demand of the growing target travellers, who are more literate and active today than in the past. They are excited followers of their favourite writers, and seek ways to be in contact with them. Now it is time to rekindle the collective memory, expand the literary dimension, and offer a sensorial in situ experience by adding a literary link. For instance, myths of the Ohlone Nation based near a California wetlands use the symbolic coyote as the intermediary to teach humans how to live in harmony with their ecosystem; or in Spain, Arcipreste de Hita’s novel El Libro de Buen Amor (1330) describes traditions and gastronomy as it criss-crosses the Guadarrama mountains, alongside the Poets’ Route that includes international Nobel prize winners in literature; Don Quijote of La Mancha (1603) was first made tangible as a literary route in 1780 ...